Bioinspired Viscoelastic Capsules: Delivery Vehicles and Beyond. Issue 27 (12th May 2019) - Etienne, Gianluca; Ong, Irvine Lian Hao; Amstad, Esther
Abstract: Microcapsules are often used as individually dispersed carriers of active ingredients to prolong their shelf life or to protect premature reactions with substances contained in the surrounding. This study goes beyond this application and employs microcapsules as principal building blocks of macroscopic 3D materials with well‐defined granular structures. To achieve this goal and inspired by nature, capsules are fabricated from block‐copolymer surfactants that are functionalized with catechols, a metal‐coordinating motive. These surfactants self‐assemble at the surface of emulsion drops where they are ionically cross‐linked to form viscoelastic capsules that display a low permeability even toward small encapsulants. It is demonstrated that the combination of the mechanical strength, flexibility, and stickiness of the capsules enables their additive manufacturing into macroscopic granular structures. Thereby, they open up new opportunities for 3D printing of soft, self‐healing materials composed of individual compartments that can be functionalized with different types of spatially separated reagents. Abstract : Calibrated viscoelastic capsules that enable triggered release of active ingredients, and that can be 3D printed into self‐healing macroscopic granular materials, are introduced. Capsules are produced from catechol‐functionalized surfactants that are ionically cross‐linked at the surface of emulsion drops. The resulting viscoelastic capsules are up‐concentrated to form an ink that is additive manufactured into 3D responsive granular materials.